Anti-aliasing multi-bit sigma-delta modulated cobweb-like disk resonator gyroscope with extending input range - Bo Fan; Shihao Du; Jingchuan Zhou; Zhenghao Lu; Dacheng Xu; Shuwen Guo; Yuyu Tan; Fang Chen (Microsystems & Nanoengineering)
Abstract A novel cobweb-like disk resonator gyroscope (CDRG) is introduced in this paper, which integrates a multi-bit electro-mechanical sigma-delta modulation (ΣΔΜ) system to significantly expand the input angular rate signal range, improving performance metrics like signal-to-noise ratio (SNR) and noise reduction. This design seeks to overcome the limitations associated with single-bit ΣΔΜ gyroscope systems by incorporating a linear multi-bit force feedback mechanism that utilizes nonlinear actuators driven by pulse density modulation. The proposed gyroscope system effectively broadens the input range without necessitating higher actuation voltages. In the absence of electronic trimming, experimental findings indicate significant enhancements in performance metrics: the input range, angle random walk, and bias instability improved by 30%, 106.2%, and 487.9%, respectively, when compared to traditional ΣΔΜ CDRG system configurations.